2002
DOI: 10.1159/000057714
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-Alpha in Combination with Ribavirin for the Treatment of Chronic Hepatitis C in Patients with Persistently Normal Aminotransferase Levels

Abstract: Background and Aims: A substantial proportion of patients with chronic hepatitis C virus infection have persistently normal serum transaminase levels. The aim of this study was to assess the efficacy and safety of interferon plus ribavirin combination therapy in this population. Methods: In this prospective open trial 152 patients with biopsy-proven chronic hepatitis C were enrolled, 32 of whom had persistently normal alanine aminotransferase levels (group A). The remaining 120 patients served as a comparison … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 17 publications
3
10
1
Order By: Relevance
“…Nevertheless, it is worth noting that the previous study by Hasan et al . (11) and our own, dealing with predominantly genotype 4 patients, are both of middle‐eastern origin, suggesting that these findings may be peculiar to our geographical region.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Nevertheless, it is worth noting that the previous study by Hasan et al . (11) and our own, dealing with predominantly genotype 4 patients, are both of middle‐eastern origin, suggesting that these findings may be peculiar to our geographical region.…”
Section: Discussionsupporting
confidence: 53%
“…In a smaller study of predominantly genotype 4 patients, Hasan et al . (11) found that the mean inflammatory and fibrosis scores were similar in patients with normal and elevated ALT. These findings are in concordance to ours, which may further suggest that ALT levels in genotype 4 patients do not reflect the histological changes.…”
Section: Discussionmentioning
confidence: 97%
“…Unfortunately, in patients with high aminotransferase levels, there is a high rate of relapse during the follow-up period. However, better results have been reported using combination therapy with IFN plus ribavirin, with an ETR rate of 40 and 47%, respectively [40,41], or with the ongoing studies using pegylated IFN and ribavirin.…”
Section: Discussionmentioning
confidence: 99%
“…2). ALT flares were usually not seen in these small combination therapy studies [58][59][60][61][62][63][64][65].…”
Section: Treatment Of Patients With 'Normal' Alt Levelsmentioning
confidence: 99%